Genotyping and phenotyping of Gallibacterium sp from poultry with respiratory clinical signs - Cotaquispe Nalvarte, Rony Yunior (2020)
The aim of this study was the phenotyping of 60 isolates of Gallibacterium sp through a profile of six families of antibiotics and their genotyping by ERIC-PCR, REP-PCR and BOXAIR techniques. It was found that 98.3% of the isolates are resistant to at least one family of antimicrobials, and 11.7% were resistant to all six families. The REP-PCR presented 45 genotypes encoded from R1 to R45, the ERIC-PCR presented 44 genotypes encoded from E1 to E44 and BOXAIR presented 56 genotypes encoded from B1 to B56, dispersed in the departments of Lima, Ica and Libertad (Peru). The study allowed to typify Gallibacterium sp and the combined use of genotypic and phenotypic methods allowed a more precise discrimination between potentially different isolates with moderate genetic diversity in the cities of Lima, Libertad and Ica.